PELATIHAN KEPADA TUKANG KONSTRUKSI UNTUK PEMBANGUNAN RUMAH SEDERHANA AMAN GEMPA Di Kecamatan Pauah Duo Kabupaten Solok Selatan - Prima Yane Putri; Risma Apdeni; Windry Novalia Jufri (Universitas Negeri Padang, 2019)
A 5.3 magnitude tectonic earthquake shook South Solok on Thursday (2/28/2019) at around 6:27 WIB. More than 479 houses were damaged, 15 units of public facilities were slightly damaged, and caused a loss of more than 25.6 billion rupiahs. The damage is mostly experienced by vernacular houses which are generally built by construction workmanship who do not understand the technical requirements for earthquake-safer housing. Therefore, local construction tradesmen as the leading element of housing development in the community, should have received more attention because it is their works that determine the strength of building structure. The use of quality building materials and construction work that refers to the basic requirements of earthquake-safer housing construction must be fulfilled, so that the built structures can become sturdier, strong, and do not endanger the inhabitants in the event of earthquake. This article presents the results of the Community Partnership Program Activities (PKM) toward construction tradesmen in Pauah Duo Subdistrict, South Solok Regency. The evaluation results showed that the average construction workmanship’s knowledge of the basic requirements of earthquake-safer housing construction increased by more than 60%. After the training, the participants have knowledge of simple technology that can be applied to housing construction and damaged house repairing activities. Keywords: Earthquake, construction workmanship, South Solok, earthquake-safer house